2015
DOI: 10.1007/s40684-015-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

A review of electrically-assisted manufacturing

Abstract: The mechanical properties of metals change temporarily or permanently under application of electric currents under deformation. This phenomenon is often referred to as electroplasticity. The electroplasticity of metals and their alloys has been investigated under various loading conditions including tensile, compressive, bending, and hardness tests. Electrically-assisted manufacturing (EAM) utilizes this electroplasticity in manufacturing processes. Due to its technical advantages such as enhanced formability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(32 citation statements)
references
References 90 publications
0
30
0
2
Order By: Relevance
“…Especially for large or complex products, this method increases the production costs [2,3]. While the application of electroplastic deformation technology allows the introduction of a cost effective and energy-saving manufacturing process of metal forming [4]. A new technology for improving the workability of Mg is based on the electroplastic effect and has already been applied in the work of Xu et al for electroplastic rolling of AZ31.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for large or complex products, this method increases the production costs [2,3]. While the application of electroplastic deformation technology allows the introduction of a cost effective and energy-saving manufacturing process of metal forming [4]. A new technology for improving the workability of Mg is based on the electroplastic effect and has already been applied in the work of Xu et al for electroplastic rolling of AZ31.…”
Section: Introductionmentioning
confidence: 99%
“…The electroplastic effect has been shown to increase formability through increasing ductility, especially in brittle metals and reducing forming loads and springback in sheet forming [2][3][4][5][6][7][8][9][10][11]. In an effort to review the current state of the art, Nguyen-Tran et al [12] summarized different EAM processes and suggested different areas of potential improvement in modeling. Ruszkiewicz et al reviewed the existing theories of electroplastic effect and different modeling approaches in their work and suggested that the electroplastic effect was based on microscale thermal softening [13].…”
Section: Introductionmentioning
confidence: 99%
“…The overall objective of this study is to determine the influence of temperature on the stretch bending quality of aluminum profiles. Since electrically assisted manufacturing has shown the advantage of modifying material properties of a metal simply by applying electricity to the metal during deformation [9], electricity was utilized to heat aluminum profiles for improving the formability and reducing the springback in this work. Firstly, stretch bending model was developed.…”
Section: Introductionmentioning
confidence: 99%